2013
DOI: 10.1111/pace.12057
|View full text |Cite
|
Sign up to set email alerts
|

Patient Specific Simulation of Body Surface ECG using the Finite Element Method

Abstract: These results not only help us understand the cellular basis of the body surface ECG, but also open the possibility of heart simulation for clinical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…Our activation sequences have been shown to replicate the main diagnostic manifestations of left anterior fascicular, left posterior fascicular, left bundle branch and right bundle branch block conditions. Previous computational studies have also shown agreement in diseased QRS biomarkers associated to left bundle branch block, using either a similar modelling approach to ours for the human activation sequence, 18 or more detailed anatomical representations of the human Purkinje network 16 . Sahli et al 17 also addressed the modelling of right bundle branch block using detailed Purkinje trees, however, without probing its impact on the precordial leads, which are the derivations used in its clinical diagnosis.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Our activation sequences have been shown to replicate the main diagnostic manifestations of left anterior fascicular, left posterior fascicular, left bundle branch and right bundle branch block conditions. Previous computational studies have also shown agreement in diseased QRS biomarkers associated to left bundle branch block, using either a similar modelling approach to ours for the human activation sequence, 18 or more detailed anatomical representations of the human Purkinje network 16 . Sahli et al 17 also addressed the modelling of right bundle branch block using detailed Purkinje trees, however, without probing its impact on the precordial leads, which are the derivations used in its clinical diagnosis.…”
Section: Discussionmentioning
confidence: 62%
“…These vary in generality, from specifying activation times analytically by means of a parameterized sequence, 15 to the creation of idealized Purkinje networks including explicit Purkinje-muscle junctions 16 , 17 . They also differ in computational complexity, from the semi-automatic generation of activation profiles, 10 , 18 to more iterative and interactive parametrization processes to converge on a personalized activation sequence 16 . The activation sequences utilized here encapsulate the minimal information needed to investigate the implication on the QRS complex of anatomical variability in the human trifascicular conduction system.…”
Section: Discussionmentioning
confidence: 99%
“…We have developed a multi-scale, multi-physics three-dimensional (3D) heart simulator in which propagation of excitation, contraction and relaxation, development of pressure, and blood flow are reproduced based on molecular models of the cardiac excitation-contraction process [13][14][15][16][17]. We also succeeded in simulating the patientspecific body surface ECG [18]. Applying these technologies, we created a tailor-made simulation model of the heart to determine if the effects of CRT could be predicted in a canine model of heart failure with LBBB [19].…”
Section: Introductionmentioning
confidence: 99%
“…Despite being computationally intensive these models have become increasingly realistic and informative. They have begun to be more widely used due to the greater availability and increase in computing power with models of the heart even being constructed for individual patients to aid diagnosis [17]. Simulations of the heart can address its electrical or mechanical properties and current models incorporate either or both of these aspects [18–20].…”
Section: Introductionmentioning
confidence: 99%